Static load test - a comparison of ultimate load between statnamic and maintained load test - Azmi, Mastura (2005)
This study is conducted to give a good comparison of the ultimate load between the statnamic load test and the maintained load test. The study was done using three methods to predict the ultimate load of statnamic load test. The three methods are the Unloading Point Method, Matsumoto method and Simultaneous Equation method. The statnamic and maintained load test was done on two types of bored pile that are bored pile cast on limestone rock and bored pile cast on granite rock. The result shown in the study gave a different outcome. From the settlement-load curves derived, the result for the comparison of statnamic and maintained load test for bored pile cast on limestone gave an almost similar result. Thus, it can be said that the result for both statnamic and maintained load test can be used to determine the ultimate capacity of the pile. Where else, the result for bored pile cast on granite rock gave a very large difference due to large difference of length for the two bored pile. Therefore, it can be conclude that the result for this study on comparison of statnamic load test and maintained load test for bored pile cast on granite can not be used.